(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Water or “blue gold” constitutes humanity its survival and posterity as a species, the importance or added value that this resource has is vital at a global level. Due to its importance, this document deals with the analysis of the United Nations World Report on the Development of Water Resources, regarding the classification of water resources by dimensions, which allows identifying the position of the United Nations based on the construction of institutional or official documents which integrate descriptive elements to understand these dimensions in a sustainable, transversal and multidisciplinary way, with the aim of contributing to the construction, management and development of a culture of water for its conservation, good management and consumption, as a good in which the State-Society relationship must combine and act in a precautionary and preventive manner for the generation of the present and future.